Polymorphisms in DNA repair genes, hair dye use, and the risk of non-Hodgkin lymphoma - Guo, Huan (Cancer Causes Control, 2014)
PURPOSE: Genetic polymorphisms in DNA repair genes and hair dye use may both have a role in the development of non-Hodgkin lymphoma (NHL). We aimed to examine the interaction between variants in DNA repair genes and hair dye use with risk of NHL in a population-based case– control study of Connecticut women. METHODS: We examined 24 single nucleotide polymorphisms in 16 DNA repair genes among 518 NHL cases and 597 controls and evaluated the associations between hair dye use and risk of overall NHL and common NHL subtypes, stratified by genotype, using unconditional logistic regression. RESULTS: Women who used hair dye before 1980 had a significantly increased risk of NHL, particularly for the follicular lymphoma (FL) subtype, but not for diffuse large B-cell lymphoma. The following genotypes in combination with hair dye use before 1980 were associated with FL risk: BRCA2 rs144848 AC+CC [odds ratio (OR) (95 % confidence interval (CI)) 3.28(1.27–8.50)], WRN rs1346044 TT [OR(95 % CI) 2.70(1.30–5.65)], XRCC3 rs861539 CT+TT [OR(95 % CI) 2.76(1.32–5.77)], XRCC4 rs1805377 GG [OR(95 % CI) 2.07(1.10–3.90)] and rs1056503 TT [OR(95 % CI) 2.17(1.16–4.07)], ERCC1 rs3212961 CC [OR(95 % CI) 1.93(1.00–3.72)], RAD23B rs1805329 CC [OR(95 % CI) 2.28(1.12–4.64)], and MGMT rs12917 CC, rs2308321 AA, and rs2308327 AA genotypes [OR(95 % CI) 1.96(1.06–3.63), 2.02(1.09–3.75), and 2.23(1.16–4.29), respectively]. In addition, a significant interaction with risk of overall NHL was observed between WRN rs1346044 and hair dye use before 1980 (p(interaction) = 0.032). CONCLUSIONS: Our results indicated that genetic variation in DNA repair genes modifies susceptibility to NHL in relation to hair dye use, particularly for the FL subtype and in women who began using hair dye before 1980. Further studies are needed to confirm these observations.